Analysis of the Factors Influencing Soybean Demand in North Sumatra Province - Hasibuan, Surtan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of the food diversification program is to encourage Indonesians to expand their dietary choices beyond rice. This initiative is not meant to replace rice but to shift consumption patterns, promoting the inclusion of a broader range of foods. Indonesia has a wealth of agricultural products, such as soybeans, corn, and potatoes, that can serve as staple foods and support the diversification effort. Given the limited purchasing power of many Indonesians, the program emphasizes food products that are both highly nutritious and relatively affordable for the general population. Legumes, including soybeans, peanuts, winged bean seeds, and koro beans, are commonly used to meet dietary needs. Among these, soybeans are particularly important as a rich source of vegetable protein. The public has increasingly turned to soybean-based products such as tofu, tempeh, soy sauce, and soy milk to boost their intake of plant-based protein. Additionally, soybeans are versatile, serving not only as food for direct consumption but also as ingredients in animal feed for poultry and fish.